Radar cross section study from wave scattering structures - Redadaa, S.; Boualleg, A.; Benslama, N. Merabtine M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Radar remote sensing deals with the extraction of object information from electromagnetic wave parameters. To fully exploit the potential of acquiring quantitative information requires a detailed description of the microwaves scattering. The research on this topic was mostly centered on far-field analysis that assumes an incident plane wave, computation of its scattered field, and evaluation of the radar cross section. However, under certain practical conditions, the far-field analysis is not valid and a near-field analysis is necessary. In this paper, we have given a full analysis of the near-field of a wedge structure due to an incident wave field from a line source or a plane wave. The far-field pattern, for the case of a line source exciting the structure, is also analyzed.